Contraception and family planning among HIV-seroconcordant and -serodiscordant couples in the US and Zambia - Deborah L Jones; Olga Villar-Loubet; Chipepo Kankasa; et al (Dove Medical Press, 2010)
Deborah L Jones1, Olga Villar-Loubet1, Chipepo Kankasa2, Ndashi Chitalu2, Miriam Mumbi2, Stephen M Weiss11Department of Psychiatry and Behavioral Sciences, University of Miami Miller School of Medicine, Miami, FL, USA; 2Department of Paediatrics, University of Zambia School of Medicine, Lusaka, ZambiaAbstract: With the advent of antiretroviral therapy, remarkable progress has been made in the reduction of morbidity and mortality associated with the human immunodeficiency virus (HIV). As a result, in both the developed and developing world, reproductive decision-making and family planning has re-emerged as an important health issue among HIV-seroconcordant and -serodiscordant couples. This study sought to explore contraceptive attitudes and practices among HIV-seropositive and -serodiscordant couples in the US and Zambia and to compare contraceptive decision-making between seroconcordant and discordant couples. Study results suggest that while most participants expressed a willingness to use protection to prevent pregnancy, the majority were not using protection consistently. Similarly, among seropositive younger men in both the US and Zambia, more men expressed a desire to have children than women of either serostatus group. Study outcomes also suggest that male and female condom use to reduce HIV transmission within couples is limited. Thus, as males are largely the sexual decision makers regarding condom use, women’s attitudes or plans regarding child bearing may be eclipsed by those of their male partners, and recent reductions in provision of female condoms in the developing world may further reduce women’s options to protect themselves and prevent pregnancy. Education and counseling on vertical and horizontal transmission of HIV among both seropositive and serodiscordant couples should be an element of family planning efforts. Conversely, family planning should be a critical element of HIV counseling and testing strategies to realistically respond to the desires of both members of the couple.Keywords: urban, decision-making, condom use, HIV transmission